THE EFFECT OF CONCRETE QUALITY AND SUBGRADE CBR ON CRACK WIDTH IN RIGID PAVEMENT: AN EMPIRICAL MODEL APPROACH - Wisnumurti, Wisnumurti; Nuralinah, Devi; Martin Simatupang, Roland (Journal of Applied Engineering Science, 2025)
In rigid pavement work especialy for rural areas, two factors that often-become problems are the quality of the concrete and the compactness of the subgrade soil, especially for the construction using labor-intensive method. Cracks on road pavement always start with a small crack width but could result in more significant damage. Thus, this research was carried out to study the influence of concrete quality and CBR value of subgrade on crack behavior in rigid pavement, as well as to obtain an empirical formula that can be used to predict maximum crack width for various steel stress, concrete quality, and CBR value of subgrade. During the experiment, loading was carried out statically and as line loads, at maximum load of 200 kN. The dimensions of the specimen were L × W × H = 200 × 60 × 20 cm, with a reinforcement ratio of ρ=0.0105 and fy 400 MPa. Designed concrete quality was 10 MPa, 20 MPa, and 30 MPa, and the designed CBR values of the subgrade were 5%, 8.5%, and 12%. Experimental results show that both concrete quality and CBR value of subgrade are in inverse relationship with the maximum crack width, while steel stress has a linear relationship. Eventhough both parameters influence the maximum crack width, but the CBR value of the subgrade has more significant influence on reducing the crack width than concrete quality. The empirical formula that can be used to predict the maximum crack width obtained from this experiment is . The increase of 50% on CBR value could reduce the maximum crack width up to 30.57%, while the similar increase on concrete quality only reduces the crack width by 11.45%. Hence, the implication of how the variables influenced the crack behavior can be seen from this proposed equation.
Keywords: concrete quality, CBR, crack width, crack behavior, rigid pavement